Use of Cone-Beam Computerized Tomography for Evaluation of Bisphosphonate-Associated Osteonecrosis of the Jaws in an Experimental Rat Model - Cankaya, Abdulkadir Burak (Ivyspring International Publisher, 2011)
Background: Bisphosphonate-induced osteonecrosis of the jaw (BONJ) is a frequently reported complication. The aim of this study was to investigate the clinical and histopathological presentation of BONJ with the Hounsfield score and to evaluate the reliability of the score for determining necrosis in an animal model. Material/Methods: Eighty rats were prospectively and randomly divided into two groups of 40 each: a control group and an experimental group. Half of the animals from each group underwent extraction of the left mandibular molars, and the other half underwent extraction of the left maxillary molars under pentobarbital-induced general anesthesia. All animals were euthanized 28 days after tooth extraction. Maxillae and mandibles were extracted, cone beam computed tomography (CBCT) was performed, and Hounsfield scores were evaluated. Results: The Hounsfield scores of the experimental group were found to be compatible with chronic osteomyelitis and periosteal reactions. The Hounsfield scores of the control group were compatible with a healthy healing period. Conclusion: In light of these results, both cone beam computed tomography (CBCT) and the Hounsfield Units (HU) evaluations together are thought to be efficient in the diagnosis of BONJ.